An adoption of Halal food recognition system using Mobile Radio Frequency Identification (RFID) and near field communication (NFC) - Khosravi, Mohsen; Karbasi, Mostafa; Shah, Asadullah; Brohi, Imtiaz Ali (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This study is focused on validating halal status for food products by using Radio Frequency Identification (RFID) or Near Field Communication (NFC) technology to enhance existing methods in Malaysia. In this research, an effective method to identify and confirm the food status is proposed. Besides, designing a database of halal products, halal identification and validation applications for android smart phones are considered. Investigation on advanced technologies to introduce an RFID based identification system using current smart phones and evaluation of other methods to realize the suitable method is highlighted.